IMLPEMENTASI AKUNTABILITAS DAN TRANSPARANSI UNTUK MEWUJUDKAN PEMERINTAH DAERAH YANG BERSIH - Wahyuni, Sri (Katalogis, 2015)
Accountability and transparency are two of the fundamental problems government accountabilities. The communities have not got clear information concerning the policies taken by the govrnment. Therefore, through transparent government, the communities are supposed to be well exposed to the policies to be taken by government. The government is supposed to stress on the accountability aspects in governmental bureaucratic reformation. In addition, government tranparency will certainly encourage the communities to address feedback to policies taken by the government. The thesis studied about how to adopt accountability and rtansparency in governmental affairs to create clean local governments and the constraints to adoption of accountability and transparency in clean local government. It was a normative legal research. It conseptualizet and reviewed laws as norms, rules and principles or dogmas adopted for discussing the fundamentals question addressed based on legal materials due to the characteristics of the law. It was concludec that the government accountability of Poso Regency was adopted on law Number: 32 Year 2004 about Local Government and State Regulation Number: 3 Year 2007 about Reporting by Local Government to National Government. At present the information about Local Government Reporting to Communities refers to Law Number: 23 Year 2014 about Local Government.